Design and Construction of E2-fliC Construct Using fliC Gene from Salmonella Enterica and E2 Gene from Hepatitis C Virus and its Expression in Eukaryotic System - Mohammad Mehdi Soltan Dallal; Abolfazl Keshavarz; Ebrahim Kord; Nastaran Ansari; Zamaneh Hajikhezri; Katayoun Samimi-Rad (Tehran University of Medical Sciences, 2018)
Background and Aim: At the present time one of the strategies in vaccine design is generation of fusion proteins containing (including) immunogen of infectious agents and adjuvants. In this study design and construction of E2-fliC fragment as a vaccine candid was conducted by using fliC gene from Salmonella enterica and E2 gene from hepatitis C virus. Materials and Methods: To prepare the E2-fliC construct, E2 and fliC fragments were first amplified from pBluscript-E2 and pBluscript-fliC, respectively by PCR method. To generate pcDNA-E2-fliC plasmid, E2 was subcloned into plasmid pcDNA3.1 (+) which was extracted from DH5α cells. The fliC sequence was then cloned into the pcDNA3.1-E2. To evaluate the expression of E2-fliC construct, it was inserted into the pEGFP-N3 expression vector. Then COS-7 cells were transfected with pEGFPN3- E2-fliC to evaluate the expression of the fusion protein by observation of the EGFP signal under the fluorescence microscope. Results: By development of GFP fluorescent using fluorescence microscopy the most expression of E2-fliC construct was observed at 24h after transfection. The accuracy of the recombinant plasmid pcDNA-E2-fliC was confirmed by PCR, restriction enzymes and DNA sequencing. Conclusion: Our findings suggest that E2-FliC fusion protein has expressed efficiently and most likely similar to HCV E2 protein induces immune system of mice after their immunization with pcDNA-E2-fliC.